Dynamic studies on portal haemodynamics by scintiphotosplenoportography: flow patterns of portal circulation. Issue 1 (January 1980) - Kashiwagi, T; Kimura, K; Suematsu, T; Shichiri, M; Kamada, T; Abe, H
Abstract : Scintiphotosplenoportography (SSP) was performed in 190 instances in 161 patients. No significant complications, such as severe pain or splenic haemorrhage, were encountered in any of the patients studied. Flow patterns of SSP were classified into nine groups according to the direction of collateral flow. Hepatopetal collateral flow was frequently observed in pancreatic cancer. In portal hypertension, cephalic collateral flow was more frequently observed than caudal flow. In detecting oesophageal varices, both SSP and endoscopy were performed in 81 patients. In four out of 46 patients with cephalic flow, oesophageal varices could not be observed by endoscopy. Conversely, in three out of 44 patients with oesophageal varices, SSP failed to show cephalic flow. The combined use of SSP and endoscopy would therefore provide more useful information in the management of patients with portal hypertension.